Exploring Student Experience of Game-Based Learning in Teaching Descriptive Text to Junior Highschool Student - Syamudra, Zakaria Panji; Rakhmawati; Septiansari, Ima (ICONELT, 2024)
In recent years, education has undergone significant changes driven by technological advances and innovative teaching methodologies. One approach that has received widespread attention is game-based learning (GBL), which integrates game elements into educational activities. This research aims to explore the benefits and drawbacks of implementing GBL in teaching descriptive texts in class 7C SMPN 1 Krian. This research employs a qualitative descriptive method, utilising interviews with students to explore their experiences regarding the advantages and disadvantages of GBL in teaching descriptive texts. The research results indicate that most students find GBL motivating and enjoyable for learning English. They felt that learning through games increased their interest and understanding of the material. However, technical challenges, such as device and internet connection problems, were identified as barriers.